2021
DOI: 10.1002/ijgo.13716
|View full text |Cite
|
Sign up to set email alerts
|

Major differences in the characteristics of users of the copper intrauterine device or levonorgestrel intrauterine system at a clinic in Campinas, Brazil

Abstract: Highly effective long-acting reversible contraceptives (LARCs), including intrauterine devices (IUDs) and implants, can be an excellent contraceptive choice for women wishing to avoid unplanned pregnancies. However, the method mix of IUDs, including the copper IUD (Cu-IUD) and the 52-mg levonorgestrel intrauterine system (LNG-IUS), is reported to be pitifully small (less than 5%) in 63 countries and only 5%-9% in a further 32 countries. 1 Compared with other contraceptives, LARC methods have lower contraceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A recent Brazilian monocentric study has only showed that users of Cu-IUDs were less likely to be nulliparous compared to users of LNG-IUSs, but it was not focused on the postpartum period. 19 In the present study, the LNG-IUS appeared to be prescribed according to French professional recommendations. The National College of French Gynecologists and Obstetricians recommends the use of LNG-IUS in absolute/relative hyperestrogenic environments, endometriosis, adenomyosis, and endometrial hyperplasia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent Brazilian monocentric study has only showed that users of Cu-IUDs were less likely to be nulliparous compared to users of LNG-IUSs, but it was not focused on the postpartum period. 19 In the present study, the LNG-IUS appeared to be prescribed according to French professional recommendations. The National College of French Gynecologists and Obstetricians recommends the use of LNG-IUS in absolute/relative hyperestrogenic environments, endometriosis, adenomyosis, and endometrial hyperplasia.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, women who had a pregnancy history in the year before dispensation of a device were more likely to get a Cu‐IUD rather than a LNG‐IUS. A recent Brazilian monocentric study has only showed that users of Cu‐IUDs were less likely to be nulliparous compared to users of LNG‐IUSs, but it was not focused on the postpartum period 19 …”
Section: Discussionmentioning
confidence: 99%
“…Users presented with high rates of satisfaction with high continuation rates and also reported non‐contraceptive benefits of the method. The number of users of this device in our service has increased in recent years 22 . Also, the benefit regarding bleeding control in women with heavy menstrual bleeding could be a reason for this choice among women with a high BMI, including after bariatric surgery 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The number of users of this device in our service has increased in recent years. 22 Also, the benefit regarding bleeding control in women with heavy menstrual bleeding could be a reason for this choice among women with a high BMI, including after bariatric surgery. 23,24 Furthermore, the ENGimplant was more commonly chosen by women with normal weight, a group in which the younger women were concentrated, and it was less commonly chosen by women with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…26 Table 2 provides a summary of the designs of the studies conducted in both public and social marketing sectors, and Table 3 lists the learning agenda questions that were addressed in countries where research was conducted (i.e., Kenya, Madagascar, Nigeria, and Zambia). Additional research was published on hormonal IUD use in LMICs during this period (2015-2021) [27][28][29] ; however, those results are not summarized here.…”
Section: Lng Iudmentioning
confidence: 99%